Palynology and sedimentology of the Pliocene Productive Series from eastern Azerbaijan. (2nd October 2021) - Richards, Keith; Vincent, Stephen J.; Davies, Clare E.; Hinds, David J.; Aliyeva, Elmira
Abstract: A palynological study of 239 outcrop samples and their sedimentological context was undertaken on the Pliocene Productive Series in the Kirmaky and Yasamal valleys, eastern Azerbaijan. The Productive Series is primarily a representation of the palaeo-Volga and forms the main hydrocarbon-producing reservoirs in the South Caspian Basin. Most sands are interpreted as fluvial, based on sedimentary characteristics. Mudstone and siltstones often contain freshwater and brackish assemblages interpreted as 'Caspian lake' transgressions, indicative of rapid Caspian Sea level change during the Pliocene. Most samples contain rich assemblages including pollen, spores, dinoflagellate cysts, algae and fungal bodies. Common tree pollen elements include Pinus, Alnus, Betula, Carya, Juglans, Pterocarya, Quercus and Ulmus, which all occur in present-day vegetation or pollen records from the Caucasus or Urals. Herbaceous pollen includes Amaranthaceae, Asteraceae (including Artemisia ), Ephedra and Poaceae, commonly found in the drier Caspian regions. The dinoflagellate cysts include 'Peri-paratethyan endemic' taxa such as Caspidinium rugosum and Spiniferites cruciformis . 'Pannonian' species such as Thalassiphora balcanica, Romanodinium areolatum and Spiniferites oblongus confirm the persistence of these taxa into the early Pliocene in Eastern Paratethys, around five million years later than their first documented presence in Central Paratethys. 'Caspian lake' influences diminish up-section, as indicated by a progression from brackish to freshwater and sub-aerial conditions. Productive Series deposition was mainly driven by the combined effects of lake level and catchment climate. The principal hydrocarbon reservoir sands were deposited as a result of increased catchment humidity, whereas drying conditions led to reduced coarse clastic input and deposition of alluvial plain mudstones. Productive Series deposition terminated with the onset of the marine-influenced Akchagyl Series, which spans the Plio-Pleistocene boundary. The lowermost sediments of the Akchagyl Series are freshwater in origin and grade up-section into marine beds containing dinoflagellate cysts of Arctic affinity.